(untitled) (Dermatology Reports, 2022)
Alopecia Areata (AA) is an autoimmune disorder characterized by hair loss, due to a T-lymphocyte-mediated inflammatory response targeting anagen-phase hair follicles. Former studies have suggested that vaccination and viral infections may play a role in the onset of AA through a variety of different mechanisms. We report here two cases of AA following COVID-19 vaccination.